Impact of implantation technique on conduction disturbances for TAVR with the self‐expanding portico/navitor valve. Issue 2 (21st December 2022) - Wang, Xi; Wong, Ivan; Bajoras, Vilhelmas; Vanhaverbeke, Maarten; Nuyens, Philippe; Bieliauskas, Gintautas; Jørgensen, Troels Højsgaard; Chen, Mao; De Backer, Ole; Sondergaard, Lars
Abstract: Background: Use of a right−left (R−L) cusp overlap view for transcatheter aortic valve replacement (TAVR) with self‐expanding valves has recently been proposed aiming to reduce permanent pacemaker implantation (PPMI). An objective, data‐driven explanation for this observation is missing. Aims: To assess the impact of different implantation techniques on the risk of PPMI following TAVR with the Portico/Navitor TM transcatheter heart valve (THV; Abbott). Methods: A TAVR‐population treated with Portico/Navitor TM had the THV implanted in a right versus left anterior oblique (RAO/LAO) fluoroscopic view with no parallax in the delivery system. The impact of these different implantation views on the spatial relationship between THV and native aortic annulus and the risk of conduction disturbances and PPMI after TAVR was studied. Results: A total of 366 matched TAVR patients were studied: 183 in the RAO group and 183 in the LAO group. The degree of aortic annulus plane tilt was significantly smaller in the RAO versus LAO group (median: 0° vs. 23°, p  < 0.001), with no plane tilt in 105 out of 183 cases (57.3%) in the RAO group. At 30 days after TAVR, the overall PPMI and guideline‐directed PPMI rates were 12.6% versus 18.0% ( p  = 0.15) and 8.2% versus 15.3% ( p  = 0.04) in the RAO versus LAO group, respectively. Conclusions: Use of a R−L cusp overlap (RAO‐caudal) view for implantation of the Portico/Navitor TM valve results in less tilt of the native aortic annulus plane and a clear trend toward a lower 30‐day PPMI rate as compared to TAVR using the conventional LAO implantation view.